A study on the pattern of skin diseases among migrant labourers visiting a teaching hospital - Senapathi, Pradeep; Kumar, Hemant; Kamath, Shama; S., Nischitha; V., Mahesh; Bhandary, Pradyumna (International Journal Of Community Medicine And Public Health, 2018)
Background: Skin diseases are quite common among migrant workers, yet little research has been done to determine their prevalence and risk factors. Poor living conditions, over-crowding, low standards of personal hygiene and environmental sanitation make them even more vulnerable. The objective of the study was to assess the prevalence and pattern of skin infections among migrant labourers and their relationship with selected socio-demographic factors. Methods: A hospital based cross sectional study was carried out among 300 temporary migrants visiting dermatology OPD of A.J. Institute of Medical Sciences teaching hospital. The duration of study was two months. All patients were diagnosed clinically by qualified dermatologists and supported by relevant investigations. Results: Most of the migrants were males (62%) while remaining (38%) were females. Majority of the migrants (42.3%) belonged to 20-40 years age group. Infectious skin diseases were found among 64.3% of the study subjects while 34.7% of them had non-infectious skin diseases. The lesions were mainly over head and neck (23.3%) followed by abdomen (23%), upper limbs (21.3%) and lower limbs (21.3%). Conclusions: The study revealed a high prevalence of infectious skin diseases among the migrant workers.